3D Printed Microtransporters: Compound Micromachines for Spatiotemporally Controlled Delivery of Therapeutic Agents. (28th September 2015) - Huang, Tian‐Yun; Sakar, Mahmut Selman; Mao, Angelo; Petruska, Andrew J.; Qiu, Famin; Chen, Xue‐Bo; Kennedy, Stephen; Mooney, David; Nelson, Bradley J.
Abstract : Functional compound micromachines are fabricated by a design methodology using 3D direct laser writing and selective physical vapor deposition of magnetic materials. Microtransporters with a wirelessly controlled Archimedes screw pumping mechanism are engineered. Spatiotemporally controlled collection, transport, and delivery of micro particles, as well as magnetic nanohelices inside microfluidic channels are demonstrated.